ANALISIS SISTEM AKUNTANSI PENGADAAN DAN PENDISTRIBUSIAN BERAS PADA PERUSAHAAN UMUM BADAN URUSAN LOGISTIK (BULOG) SUB DIVISI REGIONAL BAUBAU - Astria Putri Ning; Ishak Awaluddin; Fitriaman (Accounting Student Series on Emerging Trends, 2026)
The purpose of this study is to analyze the accounting system used in the process of rice procurement and distribution at Perum BULOG Sub Divre Baubau, as well as to evaluate the effectiveness of its implementation in practice. The research method applied is descriptive qualitative, with data collected through interviews, observations, and documentation.The results of the study indicate that the accounting system for rice procurement through Mitra Kerja and the distribution system through Rumah Pangan Kita (RPK) have been carried out in accordance with Perum BULOG’s standard operating procedures (SOP). However, there are still some manual stages, so the procurement and distribution processes are not yet fully optimal. This study recommends improvements to the workflow by using existing documents, such as the Lembar Hasil Pemeriksa Kualitas (LHPK) and Nota Timbang, to automatically trigger the payment process in order to increase efficiency and transparency. It also suggests a one‑step submission and ordering system to speed up the delivery of goods. These recommendations are expected to enhance the efficiency, effectiveness, and accountability in managing rice at Perum BULOG Sub Divre Baubau.